2006
DOI: 10.1093/brief-treatment/mhl007
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity and Situation-Specific Drinking in Women With Alcohol Problems

Abstract: We examined the unique contributions of depression, anxiety, and anxiety sensitivity (AS) in predicting frequency of drinking in different high-risk situations among 60 women receiving treatment for alcohol problems. Participants completed the Beck Depression Inventory-II, Beck Anxiety Inventory, Anxiety Sensitivity Index, and Short Form Inventory of Drinking Situations (IDS-42). Together, the negative emotionality variables reliably predicted scores on the IDS-42 negative and temptation drinking situations su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…One explanation may be that in situations where many friends are present (including potential romantic partners), young adult women who score high on coping motives use alcohol as a means to overcome nervousness, insecurity, and self-consciousness in social situations. This interpretation is consistent with several studies suggesting that social concerns, anxiety sensitivity, and coping motives are important factors in predicting alcohol use among women (Reyno et al 2006; Stewart et al 1995; Stewart et al 2001). As has been argued previously, adolescent women may use alcohol as a means to ease anxiety (Kuntsche et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…One explanation may be that in situations where many friends are present (including potential romantic partners), young adult women who score high on coping motives use alcohol as a means to overcome nervousness, insecurity, and self-consciousness in social situations. This interpretation is consistent with several studies suggesting that social concerns, anxiety sensitivity, and coping motives are important factors in predicting alcohol use among women (Reyno et al 2006; Stewart et al 1995; Stewart et al 2001). As has been argued previously, adolescent women may use alcohol as a means to ease anxiety (Kuntsche et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…In terms of intimate drinking, a daily process study by Mohr and colleagues (2001) showed on days with elevated interpersonal conflict, undergraduates high in neuroticism (i.e., a dispositional tendency toward negative affect) drank more frequently at home. Likewise, Reyno et al (2006) demonstrated that in women with alcohol problems, elevated depressive symptoms predicted heavy drinking in situations involving conflict with others. One central theoretical limitation of extant work is that no study to date has examined the mediating roles of solitary and intimate drinking contexts in depression-related drinking.…”
mentioning
confidence: 99%
“…According to SLT, the heightened negative emotionality when alone may lead to solitary drinking in an effort to dampen loneliness and isolation (Castellanos-Ryan & Conrod, 2012). Given that depressive symptoms are also associated with interpersonal difficulties (Beach, Jones, & Franklin, 2009), undergraduates with elevated depressive symptoms may also drink in intimate settings to cope with interpersonal distress and low mood (Reyno, Stewart, Brown, Horvath, & Wiens, 2006). In turn, SLT indicates that it is through frequent self-medication drinking in solitary and intimate contexts that depressive symptoms predict heavy use and alcohol-related problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AS predicts alcohol use in contexts such as interpersonal conflicts or physical discomfort, whereas in more affectively positive settings such as pleasant times with others, AS is unrelated to alcohol use (DeHaas et al, 2001(DeHaas et al, , 2002Reyno et al, 2006). In addition, individuals with high AS report particularly more alcohol use in negative emotion situations than do low-AS individuals, in both clinical (DeHaas et al, 2001(DeHaas et al, , 2002Reyno et al, 2006) and nonclinical populations (Samoluk & Stewart, 1998). Individuals with high AS also have higher sensitivity to the fear-dampening effects of alcohol than do individuals with low AS (MacDonald, Baker, Stewart, & Skinner, 2000;Stewart & Pihl, 1994;Zack, Poulos, Aramakis, Khamba, & MacLeod, 2007), which likely contributes to the motivation for high-AS individuals to drink alcohol in stressful situations.…”
mentioning
confidence: 99%